Design of a suspended high-stability fluxgate sensor. (29th March 2021) - Wang, Xiaomei; Teng, Yuntian; Fan, Xiaoyong; Wang, Chen; Wu, Qiong; Ma, Jiemei
Abstract: To achieve long-term geomagnetic vector field measurements, high resolution, low noise, reliability, and great stability are required, relative to the recording instrument. In this paper, we report the design and production of a high-performance magnetometer based on the fluxgate effect. To avoid drift due to the tilt of the observation pillar, which is often the main cause of baseline drift, and leveling error due to the installation process, the developed sensor was fixed to a suspended platform for automatic horizontal leveling. A special gimbaled construction was used, which allowed automatic leveling of the vertical position of the z -axis within tilts of ±6° of arc. The performance of the proposed sensor was tested in a zero-magnetic-field device, and the results showed that the accuracy of the scale factor was 0.01%, the standard deviation of the residuals was 0.1723, and the noise was ⩽0.08 nT (Peak-Peak). At the time of this research, the developed instrument had been in continuous operation for >6 months in the Jinghai geomagnetic observatory. The monthly residual standard deviation maximum values of the D, H, and Z components were 0.68 nT, 0.58 nT, and 0.44 nT respectively, which were smaller than the requirements of the China Geomagnetic Network. Therefore, the observational data and the baseline values indicated that the prototype was stable and reliable. Additionally, owing to its integrated design, the prototype was easy to carry and set up, so it was very suitable for short-term earthquake tracking and the intensive monitoring of magnetic anomaly areas.